Ethical and Information Governance Considerations for Promoting Digital Social Interventions in Primary Care - Georgios Dimitrios Karampatakis; Helen E Wood; Chris J Griffiths; Nathan C Lea; Richard E Ashcroft; Bill Day; Neil Walker; Neil S Coulson; Anna De Simoni (JMIR Publications, 2023)
Promoting online peer support beyond the informal sector to statutory health services requires ethical considerations and evidence-based knowledge about its impact on patients, health care professionals, and the wider health care system. Evidence on the effectiveness of digital interventions in primary care is sparse, and definitive guidance is lacking on the ethical concerns arising from the use of social media as a means for health-related interventions and research. Existing literature examining ethical issues with digital interventions in health care mainly focuses on apps, electronic health records, wearables, and telephone or video consultations, without necessarily covering digital social interventions, and does not always account for primary care settings specifically. Here we address the ethical and information governance aspects of undertaking research on the promotion of online peer support to patients by primary care clinicians, related to medical and public health ethics.